2019
DOI: 10.3390/ijms20205018
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determination of Lysosphingomyelin-509 and Discovery of Novel Class Lipids from Patients with Niemann–Pick Disease Type C

Abstract: Niemann–Pick disease type C (NPC) is an autosomal recessive disorder caused by the mutation of cholesterol-transporting proteins. In addition, early treatment is important for good prognosis of this disease because of the progressive neurodegeneration. However, the diagnosis of this disease is difficult due to a variety of clinical spectrum. Lysosphingomyelin-509, which is one of the most useful biomarkers for NPC, was applied for the rapid and easy detection of NPC. The fact that its chemical structure was un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 38 publications
(47 reference statements)
2
26
0
Order By: Relevance
“…This study aimed to characterize novel NPC disease biomarkers in order to establish a set of biomarkers for NPC that are focused on interventions targeting the HSP system in NPC and the underlying cellular pathology of NPC, including altered NPC1/2 protein function and lipid metabolism. During the time of this study and its publication, it is worth noting that other biomarkers such as lyso-sphingomyelin-509 and bile acids have also shown potential as biomarkers of NPC disease [41,[48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to characterize novel NPC disease biomarkers in order to establish a set of biomarkers for NPC that are focused on interventions targeting the HSP system in NPC and the underlying cellular pathology of NPC, including altered NPC1/2 protein function and lipid metabolism. During the time of this study and its publication, it is worth noting that other biomarkers such as lyso-sphingomyelin-509 and bile acids have also shown potential as biomarkers of NPC disease [41,[48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to characterize novel NPC disease biomarkers in order to establish a set of biomarkers for NPC that are focused on interventions targeting the HSP system in NPC and the underlying cellular pathology of NPC, including altered NPC1/2 protein function and lipid metabolism. During the time of this study and its publication, it is worth noting that other biomarkers such as lyso-sphingomyelin-509 and bile acids have also shown potential as biomarkers of NPC disease [41,[51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the exact mass, HAD-MS/MS patterns, and derivatization reaction results matched completely. Thus, it was concluded that Lyso-SM-509 was PPCS [108]. From the simultaneous analysis of PPCS and SPC in the serum/plasma of 20 healthy subjects, 15 NPC, 6 other lysosomal disease, and 43 patients suspected for NPC without the NPC1 or NPC2 mutations, the metabolites in the NPC patient samples were significantly higher than the other subjects.…”
Section: N-palmitoyl-o-phosphocholine-serine Previously Referred To mentioning
confidence: 97%